PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pelanggan Cafe Mr. K Semarang) - Angga Ardantha Dewantara, 11.05.51.0005 (Students Journal of Economic and Management, 2016)
This studyaimed to examine the effect of Product Quality, Perceived Price, and Promotionof the buying decision. The population used in this study are all customers Café Mr. K Semarang. In this study, sampling was done by waiting for consumers who are conducting the visit and also the consumer has completed a visiting Café Mr. K as well as those who are willing to be the respondent. By using a random sampling method. Respondents amount 100. Techniques of analysis using multiple regression method which previously tested the validity and reliability test. In addition, this study also uses statistical test F and the coefficient of determination. The latter hypothesis test using t test. The results showed that the variables of Product Quality and Promotion positive and significant impacton the purchase decision. While the price perception variable significant negative effecton the purchase decision. Keyword: Product Quality, Perceived Price, Promotion and Purchase Decision